Aromatherapy in mental health: A brief review - Alvarado García, Paúl Alan Arkin (2019)
Aromatherapy uses essential oils as the main therapeutic agents. In the present work a brief review was made on the aromatherapy used in mental health. It describes evidence for and against the use of aromatherapy in stress, anxiety, depression, sleep disorders, cognitive disorders and other disorders; as well as data related to its safety, adverse effects, contraindications and mechanisms of action. In conclusion, aromatherapy can be considered as an option that can be used as a complement to treatments aimed to restore mental health and associated disorders.